Development of an Open Channel That Also Functions as a Wetland to Reduce Domestic Wastewater. Issue 1 (December 2021) - Pungut; Widyastuti, S; Suhartanto, E
Abstract: Besides accommodating rainfall-runoff, the drainage channel of the Dukuh Menanggal area in Surabaya also accommodates domestic wastewater. The objective of developing the function is to degrade domestic wastewater pollution that flows into the drainage channel. The wetland is applied in the drainage channel with coarse sand media, Caladium (Caladium), and Water lettuce (Pistia stratiotes L) plant according to land size planning based on existing discharge, detention time, the porosity of the planting medium, and the root zone of the applied plants. The observed properties of domestic wastewater were Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), and detergents. The result is that the treatment of domestic wastewater passes through the artificial wetland in the drainage channel. The constructed wetland can reduce the contamination content of domestic wastewater for the parameters of BOD, COD, and detergents with efficiency levels of 46%, 61.8%, and 69%, respectively.